Dislodgement and gastrointestinal tract penetration of bone cement used for spinal reconstruction after lumbosacral vertebral tumor excision: A case report. Issue 42 (October 2016) - Nagae, Masateru; Mikami, Yasuo; Mizuno, Kentaro; Harada, Tomohisa; Ikeda, Takumi; Tonomura, Hitoshi; Takatori, Ryota; Fujiwara, Hiroyoshi; Kubo, Toshikazu
Abstract: Introduction: Polymethylmethacrylate (PMMA) cement is useful for spinal reconstruction, but can cause complications including new vertebral fractures, neurological disorders and pulmonary embolism. We report a case in PMMA cement used for spinal reconstruction after tumor curettage dislodged and penetrated the gastrointestinal tract. Diagnoses: The patient was diagnosed with a retroperitoneal extragonadal germ cell tumor at age 27 years. After chemotherapy and tumor resection, the tumor remained. It gradually increased in size and infiltrated lumbosacral vertebrae, causing him to present at age 35 years with increased low back pain. Image findings showed bone destruction in the vertebral bodies accompanied by neoplastic lesions. The left and right common iliac arteries and inferior vena cava were enclosed in the tumor on the anterior side of the vertebral bodies. Lumbosacral bone tumor due to direct extragonadal germ cell tumor infiltration was diagnosed. A 2-step operation was planned; first, fixation of the posterior side of the vertebral bodies, followed by tumor resection using an anterior transperitoneal approach, and spinal reconstruction using PMMA cement. After surgery, the PMMA cement gradually dislodged towards the anterior side and, 2 years 9 months after surgery, it had penetrated the retroperitoneum. The patient subsequently developed nausea and abdominal pain and was readmitted to hospital. The diagnosis was intestinal blockage with dislodged PMMA cement, and an operation was performed to remove the cement present in the small intestine. There was strong intra-abdominal adhesion, the peritoneum between the vertebral bodies and intestine could not be identified, and no additional treatment for vertebral body defects could be performed. After surgery, gastrointestinal symptoms resolved. Conclusion: Although this was a rare case, when using bone cement for vertebral body reconstruction, the way of anchoring for the cement must be thoroughly planned to assure no cement dislodgement can occur.